Sintesis Ester Sorbitol Oleat Menggunakan Lipase dari Getah Pepaya, Candida rugosa dan Rhizopus arrhizus ( - Suhardi Suhardi; Tranggono Tranggono; Pudji Hastuti; M. Muchalal (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
The ability of lipase from Carica papaya latex, Candida rugosa and Rhizopus arrhizus to catalyze esterification of sorbitol and oleic acid to produce Sorbitol Oleat Esters (SOE) was investigated in this study. Response Surface Methodology (RSM) was employed to evaluate the effects of temperature (x1 =40-50oC), reaction time (x2=24-72 hours), concentration of enzyme (x3=25-75 units), on percentage molar conversion as well as to determine the optimum condition of this reaction in term of this factors. Based on RSM analysis using lipase from Carica papaya latex, the optimum synthesis conditions that giving 58.31% molar conversion, were : temperature of 45.15oC, reaction time 51.73 hours, concentration of enzyme 37 units. Using lipase from Candida rugosa , the optimum synthesis conditions that giving 59.49 % molar conversion, were : temperature of 45.08oC, reaction time 53.42 hours, concentration of enzyme 75 units. Using lipase from Rhizopus arrhizus, the optimum synthesis conditions that giving 61.89 % molar conversion, were : temperature of 45.01oC, reaction time 61.68 hours, concentration of enzyme 66 units. The characteristics of SOE products using lipase from Carica papaya latex and Rhizopus arrhizus were degree of esterification (DE) 1 and (DE) 2, hydrophilic lypophilic balance 7.5-8.0, and surface tension 34.8-35.1 dyne/cm. SOE products using lipase from Candida rugosa were DE 1, DE 2, and DE 3, hydrophilic lypophilic balance 3-6, and surface tension 31.18-31.83 dyne/cm. and capable to maintain emulsion of water in oil.